Development and Validity of the Nursing Care Scale and Nurse's Difficulty Scale in Caring for Dying Patients With Cancer and Their Families in General Hospitals in Japan. Issue 2 (April 2019) - Kanno, Yusuke; Sato, Kazuki; Shimizu, Megumi; Funamizu, Yuko; Andoh, Hideaki; Kishino, Megumi; Senaga, Tomomi; Takahashi, Tetsu; Miyashita, Mitsunori
Abstract : This study develops and examines the validity and reliability of 2 scales, respectively, for evaluating nursing care and the experience of difficulties providing nursing care for dying patients with cancer and their families. A cross-sectional anonymous questionnaire was administered to nursing staff caring for dying patients with cancer and their families in 4 general hospitals and a university hospital in Japan. The instruments assessed were the Nursing Care Scale for Dying Patients and Their Families (NCD) and the Nurse's Difficulty Scale for Dying Patients and Their Families (NDD). Of the 497 questionnaires sent to nurses, 401 responses (80%) were analyzed. Factor analyses revealed that the NCD and NDD consisted of 12 items with 4 subscales: "symptom management, " "reassessment of current treatment and nursing care, " "explanation to family, " and "respect for the patient and family's dignity before and after death." These scales had sufficient convergent and discriminative validity, sufficient internal consistency ( α of subscales: NCD, 0.71-0.87; NDD, 0.74-0.93), and sufficient test-retest reliability (intraclass correlation coefficient of subscales: NCD, 0.59-0.81; NDD, 0.67-0.82) to be used as self-assessments and evaluation tools in education programs to improve the quality of nursing care for the dying patients and their families.